A moda como objeto de informação: o caso do Movimento Feminista Punk Riot Grrrl - CASTRO, Kedma Lima de (Universidade Federal do Pará, 2018)
Introduction: In considering the issue of fashion as an object of information, the study aims to present the behavior and attire characteristics of the punk feminist movement Riot Grrrrl as constituents of a singular language and discourse space and, therefore, subject to further investigations by the area of Library and Information Science. Method: This is an exploratory research of bibliographic and documentary base. Results: it presents the historical scene of punk feminist movement Riot Grrrrl within the punk background, analyzing the theme of feminism, the discussion of gender and its relationship with the overall fashion context. It was revealed that the Riot Grrrrls’ behavior and attire act as way of gender and political dissent. Conclusion: the visual reinterpretation of a punk feminist movement supported in their radical ideologies and their impact on the fashion world shows the representative nature of attire and behavior as emancipatory forms in the social, configured as discourse spaces and, therefore, as an information attribute.